A comprehensive review on anodic TiO2 nanotube arrays (TNTAs) and their composite photocatalysts for environmental and energy applications: Fundamentals, recent advances and applications - Ikreedeegh, Riyadh Ramadhan; Hossen, Md. Arif; Tahir, Muhammad; Azrina, Abd Aziz (Coordination Chemistry Reviews, 2023)
Owing to their unique properties, the electrochemically self-organized TiO2 nanotube arrays (TNTAs) have attracted great attention as promising nanomaterials for energy and environmental photocatalytic applications. This has stimulated intensive research activities that focused on the synthesis, properties, modification and applications of these 1D nanomaterials as photocatalysts. In this review, all these aspects are fully covered in a comprehensive way that was not presented previously. The review starts with discussing the main fundamentals of the photocatalytic process using TNTAs. Then, the recent developments in the synthesis methods and modification strategies of TNTAs are presented in detail. The main photocatalytic applications of TNTAs including CO2 reduction, H2 and O2 production and pollutants degradation are also summarized, taking into consideration the research studies conducted in the last 10 years. Finally, the challenges and future recommendations for the use of TNTAs are highlighted. This review aims to provide an insightful step forward to a better understanding of TNTAs-based nanomaterials and their use as proficient photocatalysts in the future.